Effectiveness of Poster-Based Nutrition Counseling on Mothers’ Knowledge in Krembangan Selatan Health Center - Rizal Wicaksono Agung; Mujayanto; Riezky Faisal Nugroho; Dian Shofiya (Journal of Nutrition Explorations, 2025)
Stunting remains a public health problem in Surabaya, where effective educational interventions are needed to enhance maternal knowledge on balanced nutrition. This study aimed to evaluate the effect of counseling using poster media on balanced nutrition knowledge among mothers of stunted or at-risk toddlers. A quasi-experimental study with a one-group pretest-posttest design was conducted at the Krembangan Selatan Community Health Center, involving 33 mothers selected through non-probability sampling. Primary data were collected through validated questionnaires administered before and after the intervention. The counseling used posters illustrating the balanced nutrition pyramid and the "Isi Piringku" (My Plate) concept. Results showed a mean knowledge score increase from 76.06 to 84.84. The Wilcoxon signed-rank test indicated a statistically significant improvement (p = 0.001). These findings suggest that poster-based counseling effectively improves maternal knowledge. However, the absence of a control group, the small sample size, and the short follow-up period limit the generalizability and long-term interpretation of the results. Further research using a randomized controlled trial design is recommended to assess sustained behavioral changes.